Konflik Narasi Keislaman Online: Kontribusi Moderasi Islam dalam Menghadapi Gerakan Transnasionalisme - Ardiansyah, Muhammad; Setiyani, Wiwik (IAIN Kendari, 2025)
The rise of digital technology has transformed how Muslims engage with religious discourse. Social media has become a contested space between Islamic moderation—emphasizing balance and tolerance—and transnational movements promoting purification and the caliphate. This article analyzes the role of Islamic moderation as a counter-narrative to transnational ideology within the digital sphere. Using a qualitative library research method, it examines academic literature and religious policy documents. Findings reveal that Salafism utilizes social media to construct an exclusive form of religious authority, whereas Islamic moderation reinforces al-wasathiyyah values through ethical and inclusive digital literacy. The study highlights the importance of synergy between the state, religious institutions, and society in strengthening digital moderation to preserve Indonesia’s peaceful and rahmatan lil-‘alamin Islamic identity. Keywords: Islamic Moderation, Transnationalism, Social Media